2023
DOI: 10.1038/s41598-023-34992-1
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of postoperative nausea and vomiting in patients undergoing laparoscopic sleeve gastrectomy and laparoscopic distal gastrectomy: a propensity score matching analysis

Abstract: Postoperative nausea and vomiting (PONV) is a common side effect after laparoscopic surgery. The aim of the study is to investigate the variables that could predict PONV in patients who underwent laparoscopic gastrectomy. We divided patients who underwent laparoscopic gastrectomy into PONV and No-PONV groups. Propensity score matching (PSM) was applied to adjust confounding factors for further validation, and ordinal logistic regression analysis was used to identify predictors for PONV. In the ordinal logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
1
1
Order By: Relevance
“…Several studies had demonstrated that the accidence of PONV after bariatric surgery is high [19,21]. The researcher found that occurrence of PONV up to 90% in the LSG [18], which is difference with our nding.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Several studies had demonstrated that the accidence of PONV after bariatric surgery is high [19,21]. The researcher found that occurrence of PONV up to 90% in the LSG [18], which is difference with our nding.…”
Section: Discussioncontrasting
confidence: 77%
“…The current research showed that the incidence of PONV in bariatric surgery is high compared with other routine surgery [18][19][20][21]. The mechanism for the high incidence of the PONV wasn't be expounded.…”
Section: Discussionmentioning
confidence: 99%